Labile carbon limits late winter microbial activity near Arctic treeline - Patrick F. Sullivan (Nature Portfolio, 2020)
Soil microbial communities remain active throughout much of the Arctic winter, and Arctic winters are warming dramatically. Here, the authors show that persistently warm winter soils can lead to labile carbon starvation and reduced microbial respiration, despite the high carbon content of most Arctic soils.